METODOLOGI TAFSIR TABI’ TABI’IN: TELAAH ATAS KITAB TAFSIR AL-QUR’AN AL-AZIM KARYA IBNU ABI HATIM AL-RAZI - Zulfikar, Eko (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
Abstract This paper seeks to explore the tabi’ tabi’in interpretation methodology, namely Tafsir al-Qur’an al-Adzim by Ibnu Abi Hatim al-Razi. By reading it from a constructivism perspective with an analysis of intertextuality data, the writer can identify the existence of Ibnu Abi Hatim interpretation which only uses the interpretation of bi al-ma’tsur as a source of interpretation, which is based on an explanation of the Prophet’s hadith, the opinions of friends, tabi’in, and the stories of israiliyyat. While the effort in explaining al-Qur’an, the method carried by Ibnu Abi Hatim is the method of ijmali, which is interpreting verses of the Qur'an in a concise, concise, and not lengthy language. In addition, Ibnu Abi Hatim also used the muqaran method by quoting and comparing the opinions of friends and the tabi’in. For his interpretation style, the interpretation of Ibnu Abi Hatim did not reach a certain scientific discipline style, only limited to the interpretation of geographical and traditionalist locations, namely interpreting the al-Qur’an by tending to use narrations from the hadiths of the Prophet, friends, and tabi’in.